The Probation and Parole Treatment Planner, with DSM 5 Updates. - Jongsma, Arthur E. (Practice planners., 2015)
The Probation and Parole Treatment Planner provides all the elements necessary to quickly and easily develop formal treatment plans that satisfy the demands of HMOs, managed care companies, third-party payors, and state and federal review agencies.